The Influence of Digital Marketing Strategy and Risk Perception on Generation Z's Online Purchasing Behavior: Pengaruh Strategi Pemasaran Digital dan Persepsi Risiko terhadap Perilaku Pembelian Online Generasi Z - Candra, Candra (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the effect of digital marketing strategies and risk perceptions on Generation Z's online purchasing behavior in Mataram City. The approach used is quantitative with the type of causal-comparative research. A sample of 97 respondents was obtained through purposive sampling technique based on the criteria of Generation Z who actively shopped online in the last three months. Data were collected using a 5-point Likert scale questionnaire and analyzed using multiple linear regression with the help of SPSS. The results showed that digital marketing strategy (β = 0.216) and risk perception (β = 0.564) had a positive and significant effect on online purchasing behavior, with a joint influence contribution of 52.8% (R² = 0.528). The research instrument is declared valid and reliable based on the results of the construct validity test and the Cronbach's Alpha value> 0.6. This study concludes that understanding of digital strategy and risk perception are important factors in determining Generation Z's online shopping behavior. The findings provide implications for digital marketers to further emphasize an adaptive approach to the behavior of young generations who are tech-savvy and sensitive to the risks of online transactions.